2015
DOI: 10.1007/s10792-015-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Spectral domain optical coherence tomography imaging of tubercular chorioretinitis and intraretinal granuloma. Intraretinal tuberculosis: a case report

Abstract: The aim of this study is to report the clinical and spectral domain optical coherence tomography (SD-OCT) findings in a patient suffering from ulcerative colitis with bilateral tubercular chorioretinitis and intraretinal granuloma regressed with systemic antitubercular therapy (ATT). This study is a case report of a 33-year-old Bangladeshi male with ulcerative colitis treated with oral corticosteroids and azathioprine who was referred to our department with a diagnosis of central serous chorioretinopathy. Sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…In the case of intraretinal TB granuloma, OCT reveals a rounded, hyperreflective lesion in the neurosensory retina, which comprises a partially hyporeflective core underlying a hyperreflective area with surrounding neurosensory retinal detachment [ 36 ]. The presence of hyperreflective dots in the outer retina are attributed to proliferating RPE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of intraretinal TB granuloma, OCT reveals a rounded, hyperreflective lesion in the neurosensory retina, which comprises a partially hyporeflective core underlying a hyperreflective area with surrounding neurosensory retinal detachment [ 36 ]. The presence of hyperreflective dots in the outer retina are attributed to proliferating RPE.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hyperreflective dots in the outer retina are attributed to proliferating RPE. Non-homogenous localized thickening is observed in the RPE/choriocapillaris complex under the retinal lesion devoid of any dome-shaped retinal elevation [ 23 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our patient had no evidence of systemic tuberculous disease; however, cases of intraocular tuberculosis, including primary retinal tuberculosis specifically, occurring in the absence of concurrent systemic disease are well documented. 1,3,4 Structural OCT has proven useful in the diagnosis and management of ocular tuberculosis. 2,7 For example, structural OCT with enhanced depth imaging has been used to identify characteristic features of tuberculous choroidal granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal granulomas are the most frequent posterior segment manifestation of ocular tuberculosis, whereas primary intraretinal tuberculosis is more rarely reported. 1,3 Pirraglia et al 4 reported a case of an intraretinal tuberculous granuloma and demonstrated the regression of the granuloma by spectral domain OCT after the initiation of ATT. Optical coherence tomography imaging in that case revealed a round intraretinal hyperreflective lesion surrounding a hyporeflective core, which the authors postulated represented abscess surrounded by inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, results are controversial about the specific anti-TB treatment (ATT) in patients with TBU [6,12]. e most frequent ATT for patients with TBU is the use of four drugs (Isoniazid, Rifampicin, Ethambutol, and Pyrazinamide) for 2 months followed by two drugs, Rifampicin and Isoniazid, for 4 months [13][14][15]. In addition, patients with TBU may develop ocular complications which require specific treatments, such as corticosteroids for cystoid macular edema (CME) or ocular surgery in patients with cataract [16][17][18].…”
Section: Introductionmentioning
confidence: 99%